Multiple Microbial Exposures in the Home May Protect Against Asthma or Allergy in Childhood - Sordillo, Joanne E (2010)
BACKGROUND: Experimental animal data on the gram-negative bacterial biomarker endotoxin suggest that persistence, dose and timing of exposure are likely to influence its effects on allergy and wheeze. In epidemiologic studies, endotoxin may be a sentinel marker for a microbial milieu, including gram-positive as well as gram-negative bacteria, that may influence allergy and asthma through components (pathogen-associated molecular patterns) that signal through innate Toll-like receptor pathways. OBJECTIVE: To determine the influence of current gram-negative and gram-positive bacterial exposures on asthma and allergic sensitization in school-aged children. METHODS: We examined the relationship between bacterial biomarkers and current asthma and allergic sensitization in 377 school-aged children in a birth-cohort study. We then evaluated the effects of school-age endotoxin, after controlling for exposure in early life. RESULTS: Exposure to gram-negative bacteria was inversely associated with asthma and allergic sensitization at school-age (for > median endotoxin: prevalence odds ratio [POR] =0.34 [95% CI=0.2 to 0.7] for current asthma and prevalence ratio [PR]=0.77 [95% CI=0.6 to 0.97] for allergic sensitization). In contrast, elevated gram-positive bacteria in the bed was inversely associated with current asthma (POR= 0.41, 95% CI=0.2 to 0.9) but not with allergic sensitization (POR=1.07, 95% CI=0.8 to 1.4). School-age endotoxin exposure remained protective in models for allergic disease adjusted for early-life endotoxin. CONCLUSION: Both gram-negative and gram-positive bacterial exposures are associated with decreased asthma symptoms, but may act through different mechanisms to confer protection. Endotoxin exposure in later childhood is not simply a surrogate of early life exposure; it has independent protective effects on allergic disease.